The contractors - Ferguson, Hugh, BSc; Chrimes, Mike (ICE Publishing, 2014)
This title charts the development of contracting from the early days of direct labour, through the canal building of the 18th century when contractors began to emerge as a major force in construction, railway development, motorway construction, privatisation and two world wars, to the international companies of today.